Metaverse Tourism Sebagai Strategi Promosi Wisata Museum Bank Indonesia - Rizki Nurul Nugraha; Prili Diana Rosa; Madeline Ivanka (Peneliti.net, 2023)
The weakness of the tourism industry for almost two years caused by the covid 19 pandemic has made tourist attractions in Indonesia strive to promote in a unique and sophisticated way, namely by implementing metaverse tourism which emphasizes rapid technological developments. One of the museums in Indonesia that uses metaverse tourism is the Bank Indonesia Museum. The promotion of this sophisticated tourist attraction will begin to be implemented by the Museum of Bank Indonesia in 2021. The method used in this research is descriptive qualitative. Data collection techniques were carried out by means of interviews, observation, literature studies, and documentation. The purpose of this study is to find out metaverse tourism as a tourism promotion strategy at the Bank Indonesia Museum. The data obtained were analyzed using SWOT analysis. Based on the results of the SWOT analysis, Museum Bank Indonesia is advised to use metaverse tourism as an alternative tourism promotion strategy that emphasizes the sophistication of technology that has been implemented. This strategy will increase awareness and experience for tourists, who will later share their experiences after visiting the Bank Indonesia Museum either through speech, writing, interesting photos or videos by uploading them on social media.